2009
DOI: 10.1111/j.1095-8649.2009.02478.x
|View full text |Cite
|
Sign up to set email alerts
|

Female ornamentation and egg carotenoids of six sympatric gobies

Abstract: Belly colouration, gonad carotenoid concentration and skin transparency were quantified in gravid Gobiusculus flavescens, as well as in females of five sympatric gobies where belly ornamentation has not been described. Although G. flavescens females did, indeed, have far more colourful bellies than the other species, this could only in part be explained by a high concentration of total gonad carotenoids. Comparable, or occasionally higher, carotenoid levels were found in the gonads of other species. Instead, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…herbivory (Alvim & Peret, 2004). Pigments such as astaxanthin, lutein, taraxanthin, and other carotenoids on the yellow ⁄orange yolk coloration have been largely studied in species feed on Krill copepods from temperate waters (Goodwin, 1986;Svensson, Blount, Forsgren, & Tamudsen, 2010). On the other hand, there are no conclusive studies on neotropical fish species about the origin, composition, and function of the carotenoids on the yolk.…”
Section: Discussionmentioning
confidence: 99%
“…herbivory (Alvim & Peret, 2004). Pigments such as astaxanthin, lutein, taraxanthin, and other carotenoids on the yellow ⁄orange yolk coloration have been largely studied in species feed on Krill copepods from temperate waters (Goodwin, 1986;Svensson, Blount, Forsgren, & Tamudsen, 2010). On the other hand, there are no conclusive studies on neotropical fish species about the origin, composition, and function of the carotenoids on the yolk.…”
Section: Discussionmentioning
confidence: 99%
“…Pink belly colour displayed by female M. ramirezi may communicate spawning readiness to males. Studies have shown a correlation between brightness of belly colour and timing of egg development and spawning, making belly colour an effective signal of readiness to spawn (Amundsen & Forsgren, 2001;Baldauf et al, 2011;LaPlante, 2015;Svensson et al, 2009). For example, belly colour displayed by female…”
Section: Discussionmentioning
confidence: 99%
“…Male mate choice for female ornamentation is widely documented in sex-role-reversed species (Berglund et al, 1986;Berglund & Rosenqvist, 2001), and there is growing evidence among species with "conventional" sex roles, including several examples observed in fishes (Amundsen & Forsgren, 2001;Baldauf et al, 2010;Edward & Chapman, 2011;Massironi et al, 2005;McLennan, 1995;Rowland & Sevenster, 1985;Svensson et al, 2009). Male choosiness is expected when females noticeably differ in quality (Kraak & Bakker, 1998;Parker, 1983), males invest more in parental care than do females (Trivers, 1972), sperm reserves are limited (Nakatsuru & Kramer, 1982) and operational sex ratio (OSR) is female biased (Clutton-Brock, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in fish: Ahmadi et al, ; Pike et al, , and birds: Blount et al, a; McGraw et al, ]. Furthermore, many vertebrates use carotenoids for integumentary coloration µamphibians: Frost and Robinson, ; Richardson et al, , reptiles: Steffen et al, , birds: Larcombe et al, , fish: Svensson et al, ], which may function in breeding behavior µe.g. in birds: Williamson et al, ], territoriality µe.g.…”
Section: Introductionmentioning
confidence: 99%